Thermoelectric Power of Amorphous InAs Thin Films - Al-Maiyaly, B. K..H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The thermoelectric power (S) of thermal evaporated a-InAs films were measured in the temperature rang (303-408) K. These films were prepared at different thickness (250,350,450) nm and treated at different annealing temperatures (303,373,423,473,523) K. The behaviour of the thermoelectric power studies of these films as a function of thickness and annealing temperature showed the thermoelectric power an increasing trend with annealing temperature ,whereas it decreases as the film thickness increases.